Band of brothers or dysfunctional family? : a military perspective on coalition challenges during stability operations - Glenn, Russell W. (Rand Corporation monograph series., 2011)
Counterinsurgency and other stability operations seldom present a nation with trials that threaten its very survival, barring cases in which that nation is the target of insurgents. Bonds between coalition members are therefore weaker than when threat of annihilation reinforces mutual dependence. Such situations are further complicated by the use of force likely not being the primary implement for attaining ultimate success. Devoid of a preeminent threat and denied primary dependence on armed forces, core coalition objectives tend to be political rather than military in character and include counterinsurgency, nation building, developing government capacity, and providing humanitarian assistance -- activities often associated with stability operations. Armed forces are not staffed or trained to meet the long-term demands of many of these tasks. An alliance or coalition must therefore incorporate participation by other government agencies and -- ultimately -- that of the indigenous government and its population more than is expected during conventional combat operations. Recent contingencies have also seen commercial enterprises, militias, intergovernmental organizations, and nongovernmental organizations become key participants in these undertakings. The result is coalitions of a size seldom seen and with a number of affiliations rarely, if ever, approached before the late 20th century. This monograph investigates the dramatic expansion of challenges confronting alliances and coalitions today and thereafter considers potential solutions that include questioning the conception of what constitutes a coalition in today's world.